2005
DOI: 10.1002/anie.200501087
|View full text |Cite
|
Sign up to set email alerts
|

Tautomers of One‐Electron‐Oxidized Guanosine

Abstract: Aminic or iminic: Two tautomeric forms of oxidized guanosine have been produced by chemical radiation methods—by direct oxidation of guanosine or from the protonation of the 8‐bromoguanosine electron adduct—and identified. The tautomerization from the iminic to the aminic arrangement has an activation energy of 23.0 kJ mol−1 and occurs through a complex transition state (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(87 citation statements)
references
References 19 publications
7
79
0
1
Order By: Relevance
“…The preferred stability of G(N 1 -H) • over G(N 2 -H) • has also been found in earlier theoretical and experimental studies. 9a,19, 20 …”
Section: Resultsmentioning
confidence: 99%
“…The preferred stability of G(N 1 -H) • over G(N 2 -H) • has also been found in earlier theoretical and experimental studies. 9a,19, 20 …”
Section: Resultsmentioning
confidence: 99%
“…þ . These questions have been treated by a number of authors employing both theory and experiment [142][143][144][145][146][147][148][149][150][151][152][153][154][155][156][157][158] without definitive conclusions. Recently, electron spin resonance (ESR) and the B3LYP/6-31G(d) level of theory have been used to identify the preferred site of deprotonation from guanine radical cation (G .…”
Section: -144mentioning
confidence: 99%
“…Similar conclusions were also drawn by Naumov and Sonntag 158 using UV-visible spectral properties and DFT study recently. Chatgilialoglu et al 155,156 also studied the tautomers of one-electron-oxidized guanosine using UV-visible spectral properties and the DFT method. Based on DFT results, they proposed the presence of a transient species G (N2-H) .…”
Section: Interestingly G(n1-h)mentioning
confidence: 99%
“…20 From ESR and pulse radiolysis experiments it is found that the G •+ deprotontes either from its N1 or N2 site to form neutral radicals • G N1 and • G N2 , respectively. 10,20,21 The transiently formed • G N1 and • G N2 in DNA disrupt the normal hydrogen bonding pattern with its complementary hydrogen bonded cytosine and results in the formation of slipped hydrogen bonded but still based paired structure. 10,11b,,22 In this work, we initially investigated the reaction of • G N1 and • G N2 with the neutral cytosine base to form the radicals G N1 (N1-N3)C • and G N2 (N2-N3)C • , respectively, see Table 1.…”
Section: Resultsmentioning
confidence: 99%